"The dwarf, the fool, the eunuch are all his": Venice, Carnival, Reproduction and Plague in Volpone. Issue 2 (November 2021) - Thiele, Matthew
Abstract : This essay explores the significance of setting Volpone (1606) in Venice while England was recovering from a major plague epidemic in 1603. The play directly references Venice's long history with the plague as a way of indirectly referencing England's struggle with plague in and around the time of the play's production. Doing so enables the play to address from a safer distance uncomfortable realities about plague time in a way that benefits Ben Jonson's English audience. The play alludes to plague through its references to plague-time beliefs and practices such as omens, medicine, and quarantine, and associating several characters with carrion birds would have been an unmistakable reference to plague for Jonson's audience. The theme of reproduction anxiety that runs throughout the play is also a recognizable characteristic of plague literature. Volpone's association with disease, carrion birds, monstrous births, and other plague omens and signs allows the anxiety produced by these elements to be purged at the end of the play when Volpone is cast out.